2022
DOI: 10.2147/idr.s387675
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Drug Resistance and Virulence of Candida Isolates from Patients with Candidiasis

Abstract: This article aims to provide a theoretical basis for new or adjuvant strategies to facilitate the early diagnosis and treatment of candidiasis and to determine if drug-resistant Candida would affect virulence. Patients and Methods: Our strains were collected from patients diagnosed with candidiasis in our hospital. The strains were identified by MALDI-TOF system and ITS sequencing. Antifungal sensitivity testing in vitro was performed to evaluate susceptibility of these isolates to current widely used antifung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For the identification of these clinical isolates, 1.5 μL of matrix solution (α-cyano-4-hydroxycinnamic acid; Bruker Daltonics, Billerica, MA, USA) was added to each C. albicans clinical isolate colony and mixed with 50% acetonitrile, 47.5% water, and 2.5% trifluoroacetic acid. The identification of these strains was performed using MALDI-TOF MS (Microflex, Bruker Daltonics) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the identification of these clinical isolates, 1.5 μL of matrix solution (α-cyano-4-hydroxycinnamic acid; Bruker Daltonics, Billerica, MA, USA) was added to each C. albicans clinical isolate colony and mixed with 50% acetonitrile, 47.5% water, and 2.5% trifluoroacetic acid. The identification of these strains was performed using MALDI-TOF MS (Microflex, Bruker Daltonics) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…They showed that the G. mellonella genome consists of 37 genes coding for 13 proteins, 2 rRNA, and 22 transport RNA. These results greatly contributed to the wider use of this invertebrate model and the replacement of vertebrates in biomedical research [ 48 , 49 , 50 , 51 ].…”
Section: General Characterization Of G Mellonela A...mentioning
confidence: 99%
“…(4) Within 7 days of infection, arthroconidia are formed, allowing for cycle to repeat (reprinted from [5]). About 40 species of dermatophytes have been identified, and the three main ones are Trichophyton, Microsporum and Epidermophyton [1], called keratinophilic, which means they possess the ability to decompose keratin in order to obtain a nutritional source, causing infection of the skin, hair, nails and mucous membranes [6]. Antifungal substances play an essential role in the treatment of mycoses.…”
Section: Introductionmentioning
confidence: 99%